1993
DOI: 10.1095/biolreprod48.5.1120
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Localization of Alternately Spliced mRNAs for Vascular Endothelial Growth Factor in Human Uterus and Estrogen Regulation in Endometrial Carcinoma Cell Lines1

Abstract: Repair of human endometrium after menstruation and preparation of the endometrium for implantation involves profound angiogenic changes. Vascular endothelial cell growth factor (VEGF) is a recently identified growth factor with significant angiogenic properties. Four species of mRNA encoding VEGFs were identified in human endometrium and myometrium. All species were present throughout the menstrual cycle. Two species, VEGF165 and VEGF121, were present in peripheral leukocytes, indicating tissue-specific splici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
94
0
2

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(107 citation statements)
references
References 46 publications
11
94
0
2
Order By: Relevance
“…This result extends previous reports showing that V 121 and V 165 are the predominant forms produced at the mRNA level in the uterus (3,5,7). Consistent with our in situ observations, relative expression levels of immunoreactive VEGF isoforms and specific V 189 increase in perivascular stromal cells during the same period, in contrast to the diffuse staining in the stroma observed in proliferative and early-mid secretory endometrium (5-7); the difference between faint stromal staining and presence of VEGF transcripts in stromal cells during the menstrual cycle was initially interpreted to be a consequence of differences in the sensitivity between immunocytochemistry (ICC) and RT-PCR analysis or in situ hybridization.…”
Section: V189 Expression In the Human Endometriumsupporting
confidence: 92%
See 2 more Smart Citations
“…This result extends previous reports showing that V 121 and V 165 are the predominant forms produced at the mRNA level in the uterus (3,5,7). Consistent with our in situ observations, relative expression levels of immunoreactive VEGF isoforms and specific V 189 increase in perivascular stromal cells during the same period, in contrast to the diffuse staining in the stroma observed in proliferative and early-mid secretory endometrium (5-7); the difference between faint stromal staining and presence of VEGF transcripts in stromal cells during the menstrual cycle was initially interpreted to be a consequence of differences in the sensitivity between immunocytochemistry (ICC) and RT-PCR analysis or in situ hybridization.…”
Section: V189 Expression In the Human Endometriumsupporting
confidence: 92%
“…Although previous studies have shown that E 2 regulates the expression of all VEGF transcripts in endometrial cells (3)(4)(5)(6)(7)20), the expression and modulation of VEGF isoforms during human implantation and decidualization is not yet elucidated. The present study demonstrates considerable expression of the V 189 isoform in the human endometrium (functional layer) during the mid-late secretory phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF145 has been detected as a rare VEGF mRNA species in placenta (35,36) and in several tumorigenic cell types that originated from the female reproductive system (37). VEGF121, VEGF145, and VEGF165 are secreted in the medium by cells, whereas VEGF189 and VEGF206 are sequestered by cell-surface heparin sulfates (38).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that Flt-1 is a bonafide receptor for VEGF, the expression of these three genes in the placenta establishes a very interesting paradigm. The VEGF gene is known to produce five different isoforms of VEGF by differential splicing (Houck et al, 1991a,b;Breier et al, 1992;Neufeld et al, 1994;Tischer et al, 1991;Charnock-Jones et al, 1993) and the probe used in these studies detects all 5 isoforms. The two largest isoforms are thought to re-main either cell-or extra-cellular matrix associated, whereas the three smaller isoforms exist as free polypeptides (Houck et al, 1991a).…”
Section: Flt-1 Vegf and Fzk-1 Expression Constitute An Interesting mentioning
confidence: 99%